A prospective comparative study of cosmetic satisfaction for three different surgical approaches. (July 2015) - Song, Taejong; Park, Jin-Young; Kim, Tae-Joong; Lee, Yoo-Young; Choi, Chel Hun; Lee, Jeong-Won; Bae, Duk-Soo; Kim, Byoung-Gie
Abstract: Objectives: To compare gynecologic patients' cosmetic satisfaction with surgical wounds after different approaches: laparoendoscopic single-site surgery (LESS), conventional laparoscopic surgery (CLS) and open surgery (OS). Study design: This was a prospective study. The primary outcome was the cosmetic satisfaction after LESS, CLS, or OS, measured at 1 and 6 months post-surgery using the well-validated Cosmetic Scale. Multiple linear regression analysis was used to determine whether the surgical approach was independently associated with cosmetic satisfaction or not. Results: Of 294 patients enrolled, 84 (28.6%), 129 (43.9%), and 81 patients (27.3%) underwent LESS, CLS, and OS, respectively. Cosmetic Scale scores in the LESS group at 1 month post-surgery was about 7 higher than in the CLS group and 9 higher than in the OS group ( P  < 0.001). This difference was maintained also at 6 months post-surgery ( P  < 0.001). On multiple linear regression analysis, the surgical approach was independently associated with postoperative cosmetic satisfaction ( P  < 0.001). Conclusion: Our study found that cosmetic satisfaction after LESS was highest, followed by CLS, then OS. Therefore, physicians should more assertively discuss and consider LESS for gynecologic diseases.